RTB Gender Research Agenda 2019-2021 - CGIAR Research Program on Roots, Tubers and Bananas (International Potato Center, 2019)
This Agenda presents the research approach, the priorities, and the governance required to address its three objectives, namely to: promote equality of opportunity in access to RTB innovations that lead to improvements in livelihoods among women and men end-users at local, national, regional, and global scales; increase the positive impact on gender equity of RTB’s innovation; ensure that the development and scaling of RTB innovations and its assessment are informed by high-quality and efficient research on gender. The current Agenda highlights three key areas, namely breeding, seed systems and scaling, identified as important for the concentration of efforts and collaboration with technical biophysical teams. It also emphasizes the need for close interaction with biophysical research areas and outlines some monitoring and evaluation parameters to support crosscutting gender research for 2019–2021.